PPARγ-SMAD6 axis-mediated inhibition of osteogenic differentiation is involved in BPS-induced osteoporosis - Zhenkun Weng; Xiu Chen; Jian Jiao; Zuqiang Fu; Qian Liu; Jin Xu; Hongchao Zhang; Qingzhi Hou; Dongmei Wang; Jiong Li; Shourui Wang; Zhen Zhang; et al. (Environment International)
Bisphenol S (BPS) is extensively utilized in personal care products, foods, and paper products, raising growing concerns about its potential environmental hazards. However, few studies have reported the effects of BPS exposure on bone homeostasis. In this study, using data from the National Health and Nutrition Examination Survey, we found a negative correlation between urinary BPS and bone mineral density (BMD). To further investigate the underlying mechanisms, C57BL/6 mice were exposed to a human-equivalent dose of BPS for 6 months. Micro-CT analysis demonstrated reduced femoral BMD in the mice, indicating that osteoporosis was caused by chronic exposure. RNA-seq analysis showed that BPS activated PPARγ in human primary mesenchymal stem cells (MSCs). Additionally, 3D molecular docking confirmed a direct interaction between BPS and PPARγ. Bioinformatics analysis identified SMAD6 as a downstream target of PPARγ. Mechanistically, the BPS-PPARγ interaction activated PPARγ, promoting SMAD6 transcription, which inhibited the osteogenic differentiation of MSCs. High-throughput virtual screening further revealed that olodanrigan effectively blocked the BPS-PPARγ interaction, and in vitro assays revealed that olodanrigan blocked the inhibition of osteogenic differentiation of MSCs induced by BPS. Additionally, olodanrigan supplementation inhibited PPARγ levels, thereby reversing BPS-induced osteoporosis. In summary, this study elucidates the role of the PPARγ-SMAD6 axis in mediating BPS-induced osteoporosis and highlights olodanrigan as a promising therapeutic intervention, offering new insights into the health risks posed by BPS and potential targets for treatment.